Bioarchaeology - Martin, Debra L. author. aut Link
XVII, 262 p.
Keywords: Bioarchaeology is the analysis of human remains within an interpretative framework that includes contextual information. This comprehensive and much-needed manual provides both a starting point and a reference for archaeologists, bioarchaeologists and others working in this integrative field. The authors cover a range of bioarchaeological methods and theory including: Ethical issues involved in dealing with human remains Theoretical approaches in bioarchaeology Techniques in taphonomy and bone analysis Lab and forensic techniques for skeletal analysis Best practices for excavation techniques Special applications in bioarchaeology With case studies from bioarchaeological research, the authors integrate theoretical and methodological discussion with a wide range of field studies from different geographic areas, time periods, and data types, to demonstrate the full scope of this important field of study. .